Validação clínica do diagnóstico de enfermagem padrão ineficaz de alimentação do lactente - Diniz, Camila Maciel (2022)
Communication between nurses is facilitated using nursing taxonomies. The use of nursing diagnoses allows professionals a standardized and objective language. However, some difficulties are encountered when using these classification systems, which jeopardizes the process of correct diagnostic inference. In the context of infant feeding, diagnostic labels have structural and conceptual limitations, for example the diagnosis Ineffective Infant Feeding Pattern. Thus, the development of clinical validation studies is important to reduce the gaps and inconsistencies observed in nursing diagnoses. Therefore, the objective of the study is to clinically validate the nursing diagnosis Ineffective infant feeding pattern. For this, infants between one month and 24 months of age were selected, followed up in a non-governmental institution specialized in early childhood care in situations of social and food vulnerability. Anamnesis was performed to obtain sociodemographic, clinical, and subjective data. The physical examination evaluated the child's health status, such as weight for age, length for age, BMI for age, child developmental milestones, skin and mucosal integrity, oral feeding conditions (sucking, chewing and swallowing). The data were organized in spreadsheets in Excel software and analyzed with the aid of the statistical program R and SPSS. Descriptive analysis was performed to obtain absolute frequencies, percentages, measures of central tendency and dispersion. To verify adherence to normality, the Shapiro-Wilk test was used. The accuracy of the diagnostic elements was obtained through latent class analysis. Adjustments to the models obtained were performed to find the one that best presents itself for the diagnosis under study, considering a likelihood ratio greater than 0.5 for sensitivity and/or specificity. The study of posterior probabilities was carried out to identify the manifestation or absence of the diagnosis according to the best-fit latent class model, considering values above 50% present. The analysis of etiological factors was carried out using logistic regression (Wald's test). The study followed the regulations for conducting research with human beings and began after approval by the Research Ethics Committee of the Federal University of Ceará and the institution listed for the study. The prevalence of diagnosis was 23%. The “Irritability” indicator showed the highest sensitivity value (90.3%). The indicators “Diarrhea”, “Choking” and “Inadequate skin and mucosal integrity” showed higher specificity values (98.9%, 98.1% and 95.9%, respectively). The etiological factors related to the infant's ineffective dietary pattern were "Oropharyngeal deformity", "Oral hypersensitivity", "Gastroesophageal reflux" and "Maternal age". Therefore, the elements identified as relevant configure a new organization for the nursing diagnosis Ineffective infant feeding pattern, making it better related to the dietary pattern context. Furthermore, such elements are suitable for interventions by nurses, except for maternal age.